2014
DOI: 10.1039/c3cc48479c
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing quantitative liquid (scanning) transmission electron microscopy

Abstract: One of the experimental challenges in the study of nanomaterials in liquids in the (scanning) transmission electron microscope ((S)TEM) is gaining quantitative information. A successful experiment in the fluid stage will depend upon the ability to plan for sensitive factors such as the electron dose applied, imaging mode, acceleration voltage, beam-induced solution chemistry changes, and the specifics of solution reactivity. In this paper, we make use of a visual approach to show the extent of damage of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
208
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(214 citation statements)
references
References 33 publications
6
208
0
Order By: Relevance
“…18,21,22,27,28 However, recent experimental observations have shown that these effects can be quantified, controlled and mitigated using calibrated electron doses. [28][29][30] As a result, in situ TEM observations can be used as an accurate starting point for understanding nanoparticle behavior in liquids.…”
mentioning
confidence: 99%
“…18,21,22,27,28 However, recent experimental observations have shown that these effects can be quantified, controlled and mitigated using calibrated electron doses. [28][29][30] As a result, in situ TEM observations can be used as an accurate starting point for understanding nanoparticle behavior in liquids.…”
mentioning
confidence: 99%
“…Such changes may not always be visible immediately, but can have long term consequences for the dynamic behavior of the sample in the gas environment [31]. Observations from liquid cell in situ TEM furthermore show that ionized species formed outside the imaged area when using an overly expanded illumination can have large effects on the observed reactions [32,33]. For these reasons, we suggest that the best practice will be to always report the areal dose-rate and illumination area and keeping the latter as closely matched to the imaged area as possible.…”
Section: Resultsmentioning
confidence: 99%
“…In this way platinum [3], gold [4], [5], and lead sulfide [6], for example, have been synthesized in situ. In these systems the electron beam facilitates reduction of an aqueous metallic salt precursor, so calibration and control of electron dose is crucial [7]. There has been some investigation of surfactant mediated nanoparticle growth [8], but for the most part in situ TEM techniques have not been applied to the wide variety of organic-phase nanoparticle syntheses.…”
mentioning
confidence: 99%
“…
Developments in in situIn these systems the electron beam facilitates reduction of an aqueous metallic salt precursor, so calibration and control of electron dose is crucial [7]. There has been some investigation of surfactant mediated nanoparticle growth [8], but for the most part in situ TEM techniques have not been applied to the wide variety of organic-phase nanoparticle syntheses.

For many nanomaterials, for example the synthesis iron oxide nanoparticles, organic phase reactions provide the necessary synthetic control [9].

…”
mentioning
confidence: 99%